Backscattered Electron Imaging of the Calcified Tissues Present in Bone Healing - Franch, J.; García, F.; Camón, J.; Manzanares, M. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
The aspect of calcified tissues involved in fracture healing was studied by means of backscattered electron imaging. Bilateral transverse midshaft osteotomies were performed in the tibiae of 16 dogs. The osteotomies were reduced by means of a type II external skeletal fixator, and the clinical and radiographic course was assessed weekly until the moment of euthanasia, one, two, four and eight weeks after the operations. The osteotomized areas were removed and their structure examined in the scanning electron microscope, using backscattered electron images, to determine the general aspect of the extracellular matrix of the calcified tissues present. Four different tissues were observed: lamellar bone, woven bone, calcified cartilage and chondroid tissue. The backscattered electron contrast and fibre arrangement of the matrix, as well as the size and shape of the cellular lacunae, allow identification of the tissue. Chondroid tissue, which seems to have a leading role in the early phases of fracture healing, shows a characteristic pattern of a highly calcified and fibrous matrix with a large number of irregular and confluent cell lacunae.The morphological characteristics of the calcified tissues involved in fracture healing were studied by means of backscattered electron imaging. Lamellar bone, woven bone, calcified cartilage and chondroid tissue were the four calcified tissues observed during the healing process of canine midshaft tibial experimental fractures.
Keywords: Backscattered electron imaging; fracture healing; calcified tissues; chondroid tissue